Community Radio Initiation for Remote Learning Program in East Nusa Tenggara - Ressi Dwiana (Center for Southeast Asian Social Studies (CESASS), 2022)
This paper reports the initiation of community radio as a remote learning medium in Sumba Island, East Nusa Tenggara, Indonesia. Using qualitative method, this study examines a community radio establishment in Sumba, an underdeveloped area in East Indonesia during the global pandemic of Covid-19. The study found out that digital divide was the key factor when the Government decided to stop face-to-face learning into online learning in March 2020. Compounded by flash floods and landslides in April 2021 in the midst pandemic, a group of civil society initiated a community radio for remote learning located in Melolo, East Sumba Regency, East Nusa Tenggara Province, providing educational services for the community.